Difference between Domestic and Hostile Applications of Wireless Sensor Networks - Haoran Yu (Big Data and Computing Visions)
Wireless Sensor Networks (WSNs) always have many potential applications and also unique challenges. They usually consist of hundreds or thousands of small sensor nodes such as MICA2, which operate autonomously conditions such as cost, invisible deployment and many application domains, such as lead to small size and limited resources sensors.